Konsep Arsitektur Islam pada Bangunan Masjid Besar di Kota Kendari - Retnaning Palupi; Lala Lestari; La Pande Jurumai (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2022)
As time progresses, architectural concepts are also developing. One of them is the concept of Islamic architecture. Mosque building is a place of worship for Muslims and also one of the applications of Islamic architecture. The application of Islamic architecture to mosques aims to present Islamic values into the building. The concept of this mosque draws from ornaments, facades, and the application of architecture to mosques and studies, especially on the mass of mosque architectural buildings, namely the visible image of the mosque, mosque plans, mosque history, architectural characteristics of the mosque, application of rules to mosque architecture, transformation of the shape of the mosque, as well as how the shape of the doors and windows on the mosque building, research using a descriptive approach obtained from the data through the process of observing objects directly taking literature / articles.